Sistem Pendukung Keputusan Penerima Bantuan Kartu Indonesia Pintar dengan Metode Weighted Product - Yuniarti, Wenty Dwi; Damayanti, Laili Zanura; Nur'aini, Siti (Jurusan Teknologi Informasi Universitas Semarang, 2023)
Education is a bridge to educate the nation s life. The government has launched various programs for equitable distribution and expansion of access to education, one of which is Program Indonesia Pintar (PIP). Smart Indonesia Card (KIP) is a marker for PIP recipients. The implementation of PIP is considered effective if KIP is given on target. SMK An Najah has implemented PIP. Each period, SMK An Najah faces many applicants with complex requirements documents. Unfortunately, the determination of KIP aid recipients is still done manually, so it takes a long time and has the potential for inaccurate targets. This study proposes the use of a computer-based decision support system using the Weighted Product (WP) method to determine KIP recipients. WP uses a multiplication technique to connect attributes ratings that have been raised to the power of weight. Based on the evaluation using User Acceptance Testing (UAT), it is known that the decision support program can be used with an acceptance rate of 79.15% or in the worthy category.